THE EFFECT OF SOCIAL MEDIA MARKETING AND ONLINE TOURISM DESTINATION REVIEWS ON TOURISTS' VISITING DECISIONS - Herlina Fransiska Br Tarigan; Riko Alexsander Manalu; Mohd. Nawi Purba; Ara Auza (Jurnal Ipteks Terapan, 2023)
The purpose of this study was to determine the effect of Social Media Marketing and Online Tourism Destination Reviews on Tourists' Visiting Decisions at the Tangkahan Tourism Object, Langkat Regency, North Sumatra. The analysis used is associative analysis, this research method is quantitative. The population in this study were all domestic and foreign tourists visiting the Tangkahan tourist attraction, Langkat Regency, North Sumatra, totaling 92,503 in 2018-2022. The sampling method uses a non-probability sampling method with an accidental sampling technique, namely a sampling technique based on coincidence, that is, anyone who happens to meet researchers at the Tangkahan tourist attraction, Langkat Regency, North Sumatra. Using the slovin formula so that the sample obtained is 100 respondents. The results obtained from this study indicate that: 1) Social media marketing has a partial and significant influence on the decision to visit tourists, 2) Reviews of online tourist destinations have a partial and significant effect on the decision to visit tourists, 3) Social media marketing and online Tourism Destination Reviews simultaneously have an influence and are significant on visiting tourists decisions. Adjusted R square value of 0.719 can be called the coefficient of determination, this means 0.719 (71.9%) Customer satisfaction can be obtained and explained by social media marketing and online tourism destination reviews while the remaining 38.9% (100% - 71.9% = 28.1%) is explained by variables outside the model that are not examined .